The role of common genetic markers in susceptibility to type 1 diabetes and autoimmune thyroid diseases - Ekaterina Alexandrovna Repina (Сахарный диабет)
This review generalizes current data on the genes responsible for combined susceptibility to type 1 diabetes and autoimmune thyroid diseases. Analysisof the role of common genetic markers facilitates understanding their contribution to the development of each of the two or several concomitantautoimmune diseases affecting a single patient